ANALISIS KEGIATAN EKSTRAKURIKULER PASKIBRA DALAM MENGEMBANGKAN NILAI KARAKTER NASIONALISME PESERTA DIDIK - Nur Alqomah Alimah; Bambang Budi Utomo; Shilmy Purnama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aimed to know the description, process, and barriers of extracurricular activities in developing the value of nationalism character to the students (the members of Paskibra) at SMAN 1 Pontianak. This research used descriptive with a qualitative form research design. The source's data of this study were Paskibra's members batch 27 classes X, trainers, coaches, the data taken from interview sheets for informants, observation sheets, and the secondary data were taken from Paskibra administrator. The results showed that the nationalism character of Paskibra members had developed and was in a good category. It was marked by an attitude of loving the homeland, appreciating the heroes' merit, having a sense of coalescence and unity, and loving the arts and culture of Indonesia through the process of implementing Paskibra activity. It aims to develop a sense of loving their homeland by raising the flag properly and correctly. However, there were also obstacles such as the limited time and field in carrying out the activities. Keywords: Character Value, Extracurricular, Paskibra